Análisis de los contenidos cinematográficos de retina latina, a partir del concepto de diversidad, en el contexto de la concentración de medios (2019)
This research seeks to understand, through the Latin American film platform Retina Latina, the problem of media concentration and its impact on the audiovisual industries' cultural diversity. To do this, the political economy of communication is proposed as an analytical perspective, a conceptual approach that allows us to establish whether there is diversity in communicational structures by analyzing three interrelated aspects: themes, agents, and users. Based on this perspective, this research characterizes, through data systematization and modeling, each of these aspects in 374 films published on Retina Latina between 2016 and 2019. From this exercise, visualization is made that accounts for the level of diversity present on this platform and reflects on its possibilities to establish itself as an audiovisual space instead of the logic of media concentration.